Competition Authorities as the Pillar of a Competitive Social Market Economy – a Case Study of Institution Building in Serbia - Jovanić, Tatjana (LeXonomica, 2017)
The European economic model benefits from market forces as conditions for achieving goals of enterprises and consumers and economic efficiency is assured by necessary market infrastructure. Competition authorities are, without a doubt, one of the crucial pillars of the (social) market economy. The strength and impact of the competition rules is determined by their efficient implementation. The modest results to date of the competition policy in transitional economies militates in favor of an increase of the institutional capacity and require strengthening of the regulatory powers of public agencies in construction of an efficient economic system. Establishing a system of competitive markets through sectoral regulation, competition protection and state aid control at the national level requires a valid solution for a variety of legal, political and institutional conflicts. As the experience of the countries of South-East Europe has shown, many difficulties arising from the establishment of a functioning control system are procedural and relate to institutional building dilemmas. The purpose of this article is to shed  light on the requirements the Republic of Serbia has to satisfy in accession negotiations, and in particular, those related to building an efficient system of state aid control.